2015
DOI: 10.5194/isprsarchives-xl-3-w3-349-2015
|View full text |Cite
|
Sign up to set email alerts
|

Uav-Borne Thermal Imaging for Forest Health Monitoring: Detection of Disease-Induced Canopy Temperature Increase

Abstract: Commission VI, WG VI/4KEY WORDS: Stress detection, unmanned aerial vehicle, unmanned aerial system, UAV, UAS, camera calibration. ABSTRACT:Climate change has a major influence on forest health and growth, by indirectly affecting the distribution and abundance of forest pathogens, as well as the severity of tree diseases. Temperature rise and changes in precipitation may also allow the ranges of some species to expand, resulting in the introduction of non-native invasive species, which pose a significant risk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 6 publications
0
46
0
3
Order By: Relevance
“…Agricultural applications have been pursued more actively than forestry applications (Mcfadyen et al 2014). There is, however, a precursor study in Europe, dealing with red band needle blight (Mycosphaerella pini Rostrup ex Munk; Mycosphaerellaceae) infection in Scots pine (Pinus sylvestris Linnaeus) (Smigaj et al 2015). This disease on pine trees also occurs in Canada (https://tidcf.nrcan.gc.ca/en/diseases/ factsheet/1000003).…”
Section: Emerging Remote Sensing Technologiesmentioning
confidence: 99%
“…Agricultural applications have been pursued more actively than forestry applications (Mcfadyen et al 2014). There is, however, a precursor study in Europe, dealing with red band needle blight (Mycosphaerella pini Rostrup ex Munk; Mycosphaerellaceae) infection in Scots pine (Pinus sylvestris Linnaeus) (Smigaj et al 2015). This disease on pine trees also occurs in Canada (https://tidcf.nrcan.gc.ca/en/diseases/ factsheet/1000003).…”
Section: Emerging Remote Sensing Technologiesmentioning
confidence: 99%
“…In special cases may a later registration of generated orthophoto to an external registered dataset (e.g. LiDAR CHM) help to properly georeference thermal orthophotos (Smigaj et al, 2015), but often are datasets not acquired within an appropriate time period, too outdated or finding corresponding features in forest canopies of blurred images is impossible. Contrast enhancement processing on the sensor level is also very important for tie point matching and future improved hardand firmware may lead to even more feasible applications.…”
Section: Discussionmentioning
confidence: 99%
“…Canopy foliage temperature is mainly dominated by the canopy geometry (shape, density, leaf size, etc. ), radiation, air-temperature and transpiration (Martynenko et al, 2016;Reinert et al, 2012;Smigaj et al, 2015). Leaf temperature measurement using thermal infrared (TIR) sensing is primarily used to study plant water relations, and specifically stomatal conductance, because a major determinant of leaf temperature is the rate of evaporation or transpiration from the leaf (Jones et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conifers represent particularly challenging targets for remote sensing analysis, mainly due to their structural features, for example, narrow needle leaves. With the exception of [28,31,32], thermography of conifer trees still remains almost unreported in the literature; therefore, the investigation of stress responses in the temperature domain is largely lacking. In Kim et al [31], the daily and sub-daily mean canopy temperatures extracted from uncorrected imagery were shown to be related to climatic and soil variables, whilst Smigaj et al [32] found a correlation between disease progression and canopy temperature increase.…”
Section: Introductionmentioning
confidence: 99%